The Epistemology and Ethics of Taklif: An Analysis of the Legal Subjectivity of the Majnūn - Alla Ahmed Alaghbri (ESENSIA: Jurnal Ilmu-Ilmu Ushuluddin, 2020)
Legal subjectivity, particularly that of the majnūn, is an understudied topic that is often only glossed over or nominaly referenced in academic scholarship on Islamic jurisprudence. In attempting to fill this gap in scholarship, this article aims at examining the epistemological and ethical dimensions of legal subjectivity, particulary as it relates to the insane. The article takes the the concept of taklif in classical Ash'arite works of jurisprudence as the center of its analysis of legal subjectivity. Taklif, it characteristics, the relationship between the law giver and the legal subject, and the host of epistemological and ethical assumptions embedded in assigning legal subjectivity to certain individuals and excluding others from it, were among the main issues that classical Muslim jurists grappled with. Understanding the concept of taklif as a form of prescriptive speech, Ash'arite jurist-theologians went on to articulate a theory of legal subjectivity that emphasized the mental capability of the legal subject to comprehend the moral import of  divine prescriptive address and to respond to it with cognizant and intentional obedience. In stressing the value of cognitive ability, Muslim jurists contended that the comprehension of insane individuals fell short of the level necessary to acquire legal subjectivity. Beyond the issue of the legal subjectivity of the insane, this study of the concept of taklif allows us to understand some of the ways Muslim jurists conceived of reason/rationality, the relationship between intentionality, knowledge and action, and the nature of divine speech and its normative value.